ANALISIS USAHA TERNAK BABI DI KABUPATEN ALOR (Analysis of pig farming businesses in Alor District) - Elci A. Gawang; Maria Y. Luruk; Obed H. Nono; Arnoldus Keban (JURNAL NUKLEUS PETERNAKAN, 2022)
A study was carried out in Alor District for one month from 24 February to 24 March 2020. This study aims to find out and analyze the income and financial feasibility of the pig farm business in Alor Regency. The research method used was a survey method to obtain primary data through direct interviews with farmers based on a list of questionairre prepared and secondary data was obtained from related agencies. Sampling was done following a procedure of multi stages sampling . The first, selecting four sample district in apurposive manner; the second, the selectionof eight villages from each selected sub-district purpossively and the third, the selection of 80 farmers by applying non-proportional random sampling. Data were analyzed using income analysis and financial analysis focussing on the criteria of R/C, B/C,BEPQ dan BEPS.. The results showed that the average income over the total cost obtained by each farmer was Rp.10,146,807/ year and the income over cash cost was RP.2,565,807 /year. Financial analysis showed that the value of R/C = 3.48, B/C = 2.48,BEPQ.= 0.29 AU and BEPS. = Rp.426.200,-.In summary, the pig farm business in Alor District was profitable and financially feasible. Therefore, this business needs to be developed and improved.